The influence of the combination of mental and cognitive maps strategies in learning the performance and accuracy of spike volleyball - Hasan, Hanan Taher; Entissar Owaied Ali (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at preparing an educational curriculum by employing the mixing of the strategies of mental and cognitive maps and identifying its effect in learning the performance of the skill of spike with volleyball and its accuracy among fifth grade students. The two researchers assumed: The application of mixing of the strategies of mental and cognitive maps has a positive role in learning to perform the performance of spike skill With volleyball and its accuracy among fifth-grade students, preparation. The two researchers adopted the experimental approach to designing the experimental groups and controlling (51) students deliberately selected at a rate of (55.914%) from Al-Mustansiriya prep in Salah Al-Din Governorate for the academic year (2019-2020). The approved tests were the skills performance tests For the skill of overwhelming multiplication and accuracy after photographing it before and after and assessing it, as they applied the learners in the experimental group by (4) educational units according to the weekly lessons schedule, (3) were devoted to learning performance and (1) to learn accuracy, as concepts that mix the two strategies were employed in flexes measuring ( 2 x 3) m is presented with the application of educational exercises to activate the role of female learners in the lesson according to the specifics and steps mentioned and after completing the experiment according to the As mentioned in the experimental design, the researcher verified the results with the Social Statistical Pouch System (SPSS-V26) to make the conclusions and applications that the application of blending the strategies of mental and cognitive maps helps in improving the learning of the performance of the overwhelming knocking skill and accuracy of students in the fifth preparatory grade, and they excel at improving their learning of their performance and accuracy For educated students in the methods used in the lesson of physical education, attention must be paid to adopting practical applications to mix educational strategies that are concerned with the knowledge structure and further strengthening the link between the performance experiences of spike skill and information accuracy in the main sections of the physical education lesson, and it is necessary to pay attention to the availability of mixes Mental and cognitive mapping strategies in volleyball halls in middle schools.